Evaluation of the Insecticidal Activity of Essential Oil Extracted by SteamDistillation from Fresh Leaves of Melaleuca leucadendronon Sitophiluszeamais, a Pest of Maize Stocks - DIOUF, El Hadji Gorgui; Adama Faye; Ababacar Diouf; Alioune Diouf; Mamadou Latyr Ndour; Mamadou Kébé; Talibouya Ndior; Alioune Ndiaye (Agriprima : Journal of Applied Agricultural Sciences, 2025)
Post-harvest losses due to insect pests represent a major challenge for cereal conservation in sub-Saharan Africa, particularly for maize storage. Conventional chemical insecticides, although effective, present risks of toxicity, environmental pollution, and the development of insect resistance. As a result, research has increasingly focused on natural, sustainable alternatives derived from aromatic plants. This study evaluates the insecticidal activity of essential oil extracted by steam distillation from fresh Melaleuca leucadendron leaves against Sitophilus zeamais, the main pest affecting maize stocks in Senegal. The extractions yielded an average of 0.75%, and GC-MS analysis revealed a composition dominated by sesquiterpenes, mainly γ-gurjunene (35.47%), nerolidol (17.47%), and farnesol (15.51%), indicating a high content of bioactive compounds. Maize grains were treated with different doses of oil (25 to 100 μL) and exposed to insects for 36 days, with adult mortality and the emergence of new generations being monitored and analyzed by ANOVA. The results show that mortality is highly dose-and time-dependent, with high doses causing total mortality on the first day, while lower doses induce a slower but longer-lasting residual effect. The emergence of new generations is significantly reduced, especially at high concentrations, and the efficacy is attributed mainly to sesquiterpenes, possibly enhanced by the synergistic effect of minor compounds. These observations suggest that M. leucadendron essential oil is a promising natural alternative to chemical insecticides for maize preservation, although further research is needed to optimize its formulation and stability and to assess its impact on grain quality.